2023
DOI: 10.3390/jcm12103591
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ureteroscopy (URS) and Stone Treatment in Patients with Recurrent UTIs: Outcomes over a 10-Year Period

Abstract: Background. The study aimed to assess whether the eradication of kidney stones might result in a substantial reduction in the onset of recurrent UTIs. Methods. We selected all the patients who underwent ureteroscopy (URS) for stone disease between 2012 and 2021, with either a history of recurrent UTIs (rUTIs), urosepsis or pre-operative positive urine culture (UC). Data included patient demographics, microbiological data, stone parameters, stone-free and infection-free rates (SFR and IFR, respectively) at foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…As most of the postoperative complication seen in the studies included in our review might be reported to pre-existing medical conditions, an accurate pre-assessment is mandatory to plan an active intervention. When the overall general health of the elderly patients makes the procedure feasible, and the life expectancy is long enough, it has been shown that an active stone treatment can affect positively the quality of life, also reducing the risks of recurrent infections and sepsis related to an untreated urolithiasis [ 23–25 ].…”
Section: Discussionmentioning
confidence: 99%
“…As most of the postoperative complication seen in the studies included in our review might be reported to pre-existing medical conditions, an accurate pre-assessment is mandatory to plan an active intervention. When the overall general health of the elderly patients makes the procedure feasible, and the life expectancy is long enough, it has been shown that an active stone treatment can affect positively the quality of life, also reducing the risks of recurrent infections and sepsis related to an untreated urolithiasis [ 23–25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The original paper by Ripa et al analyzed data of 178 consecutive patients with recurrent UTIs, sepsis, or pyelonephritis who underwent ureteroscopy and laser lithotripsy (FURSL) as a treatment for their urinary stones over a 10-year period. The study showed that 88.8% of the patients were infection-free after the treatment [14]. The overall rate of early post-operative UTI recurrences was 6.2%, with a gradual increase over time, mostly related to stone recurrence.…”
mentioning
confidence: 91%